Slow Deep Breathing Intervention to Reduce Pain Intensity in Mild Head Injury Patients - Dadi Hamdani; Rena Prizka Melia; Henri Setiawan (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2023)
Background: One of the most common factors that cause head injuries is traffic accidents. Minor head injury is a nervous system disorder caused by a violent blow or jolt to the head or body. As a result of this accident an individual can lose consciousness which is characterized by headaches and pain. Pain is a physiological problem. Interventions that can be used in overcoming pain are by providing slow deep breathing non pharmacological therapy. Purpose: This study was to obtain an overview of slow deep breathing therapy in patients with mild head injuries and reduce pain intensity. Methods: The writing used is descriptive method in the form of case studies through the nursing process approach which includes assessment, nursing diagnoses, planning, implementation and evaluation. The study was conducted at the BLUD RSU Banjar City on 27-31 May 2022. The participants in this study were the patient Mrs. S is 36 years old. Complains of pain in the back of the head. The process of assessing and establishing a diagnosis is focused on the main problem. Subjective and objective data become a reference for evaluation of nursing implementation on a regular basis. Result: Based on the assessment of the pain scale, it was found that the original scale decreased from 4 (1-10) to 1 (1-10). Using the Numeric Rating Scale (NRS) measurning instrument. Conclusion: The author found the effect after giving slow deep breathing intervention on reducing pain intensity in patients with mild head injury and getting effective results, as evidenced by a decrease in the intensity of the pain scale. From the case study, slow deep breathing intervention can be an alternative intervention for mild head injury patients so that complications from the disease do not occur.